Upaya Guru MI Tarbiyatus Shibyan dalam Meningkatkan Kompetensi Siswa pada Pembelajaran Masa Pandemi Covid-19 - Wahyuningsih, Nur Riska; Rahman, Fawait Syaiful (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
Covid-19 has an impact on all sectors of life, from economy, politics, health, social, to education. Education in Indonesia during the Covid-19 Pandemic has undergone quite a variety of adaptations, ranging from social restrictions to temporary closure of teaching and learning activities, because it is feared that there will be associations or direct contacts that trigger new clusters. One of the things that is interesting is the teaching and learning process at MI Tarbiyatus Shibyan which is positioned in a fairly remote area, and the MI according to considerations of geographical conditions allows experiencing many obstacles, including the use of technology. This research tries to explore in depth what are the efforts of MI Tarbiyatus Shibyan teachers in improving Student Competence during the Covid-19 Pandemic. This research is qualitative research, with a type of field research. The data collection method uses interview, observation, and documentation techniques. Meanwhile, data analysis uses reduction, display, and conclusion drawing. Based on the results of research and analysis obtained conclusions; first, The efforts of Madrasah Teacher Ibtidaiyah Tarbiyatus Shibyan to improve student competence are to analyze the condition of students. This analysis effort is intended to know the development and growth of students. Thus, the next step can be decided, whether the material can be continued or needs repetition of the material with different strategies and media for the equitable distribution of the student's ability to master the lesson. Second, the problems faced by MI Tarbiyatus Shibyan education staff are as follows; first problems related to finances, second problems related to learning materials, Third, problems related to facilities and infrastructure. And the four problems related to the competence of the use of information technology. The implementation of learning during the Covid-19 pandemic at Madrasah Ibtidaiyah was carried out remotely known as distance learning (PJJ) with a combination of online learning and offline learning (outside the network)